(untitled) (World Economics and Finance Bulletin, 2023)
The article focuses on the attraction of funds by enterprises to financial projects, financing and increasing the attractiveness of investment activities, as well as the effectiveness of investment activities in industrial enterprises on the basis of the Dupont model.